2015
DOI: 10.1038/jid.2015.87
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis and the Risk of Major Cardiovascular Events: Cohort Study Using the Clinical Practice Research Datalink

Abstract: The association between psoriasis and risk of major cardiovascular (CV) events (myocardial infarction, acute coronary syndrome, unstable angina, and stroke) is unclear. A cohort study with 48,523 patients with psoriasis and 208,187 controls was conducted. During a median follow-up of 5.2 years, 1,257 patients with psoriasis (2.59%) had a major CV event, compared with 4,784 controls (2.30%). In the multivariable analysis, inflammatory arthritis hazard ratio (HR) 1.36 (1.18-1.58), diabetes HR 1.18 (1.06-1.31), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
126
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(151 citation statements)
references
References 40 publications
(51 reference statements)
4
126
0
14
Order By: Relevance
“…Case definitions may also vary from study to study, for instance, previous studies using electronic health records have stratified patients using phototherapy and differing DMARDs as surrogate markers for disease severity which may not accurately classify the level of disease activity [25][26][27]. Patients must assess the benefits and risks to starting treatments, in particular, systemic and biologic therapies which may cause adverse effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case definitions may also vary from study to study, for instance, previous studies using electronic health records have stratified patients using phototherapy and differing DMARDs as surrogate markers for disease severity which may not accurately classify the level of disease activity [25][26][27]. Patients must assess the benefits and risks to starting treatments, in particular, systemic and biologic therapies which may cause adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Two inception cohorts using the Clinical Practice Research Datalink have provided opposing results; Parisi et al [25] found no increased risk of major cardiovascular events while Degran et al [26] reported an increased risk for severe psoriasis patients.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, there are also controversial results from other studies. Certain studies found equal cardiovascular risk with general population 47 . However, current guideline by the European Cardiology Association and international psoriasis organizations recognize the psoriasis as a condition increasing cardiovascular risk and suggests that patients should be managed also in this respect [48][49][50][51][52] .…”
Section: Figure 3 Psoriatic March Phenomenamentioning
confidence: 98%
“…Ancak son yıllarda, obezite, metabolik sendrom, nonalkolik yağlı karaciğer hastalığı ve kardiyovasküler hastalık (KVH) riskinin de artmış olduğu ve bunun hastalık şiddetiyle ilişkili olduğunu destekleyen veriler mevcuttur (13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Psoriasisli Hastanın Genel öZellikleriunclassified
“…Bu varsayımı doğrulamaya yönelik, çok sayıda, farklı yöntemlerle gerçekleştirilmiş araştırma vardır. Araştırmalardan elde edilen veriler çelişkili olup, bazılarında psoriatik inflamasyonun bağımsız bir risk faktörü oluşturarak KVH riskini arttırdığı, kalp krizine bağlı ölümün özellikle genç sedef hastalarında daha fazla olduğu ve yaşam beklentisinin, şiddetli sedefli bireylerde daha kısa (erkeklerde 4,4, kadınlarda 3,5 yıl) olduğu saptanmıştır (13)(14)(15)(30)(31)(32). Bazı çalışmalarda ise tüm risk faktörleri eşleştirilerek analiz yapıldığında kardiyovasküler riskin toplumla eş olduğu görülmüştür (33)…”
Section: Metabolik Sendrom Ve Kardiyovasküler Hastalıklarunclassified